2018
DOI: 10.1021/acs.jpca.8b05346
|View full text |Cite
|
Sign up to set email alerts
|

H-Atom-Forming Reaction Pathways in the Pyrolysis of Furan, 2-Methylfuran, and 2,5-Dimethylfuran: A Shock-Tube and Modeling Study

Abstract: The methyl-substituted furan derivatives 2-methylfuran (2-MF) and 2,5-dimethylfuran (2,5-DMF) are often discussed as alternative fuels. Despite the large number of mechanistic studies on the pyrolysis and oxidation of 2-MF, 2,5-DMF, and unsubstituted furan (F), detailed kinetic investigations of the initial reaction steps are scarce. In this work, we report on shock-tube studies with detection of hydrogen atoms by atom resonance absorption spectroscopy to investigate the thermal decomposition of F, 2-MF, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 54 publications
6
31
0
Order By: Relevance
“…The mechanism for the formation of propargyl (C3H3) radicals is proposed to be via formyl allene (INT3) → C3H3 + HCO (P3) by Tian et al 36 while Sendt et al 35 proposed via the formation CH3CCH (P2) → C3H3 + H pathway. The proposed pathway via CH3CCH resonates well with the conclusion of recent works by Cheng et al (2017) 98 and by Weber et al 32 who pointed out that C3H3 radical is mainly formed from C3H4 isomers rather than from furan directly. Moreover, Urness and co-workers 31 determined the fraction of propargyl (C3H3) radical to propyne (CH3CCH) using a silicon carbide microtubular reactor and found that the [C3H3]/[CH3CCH]) branching ratio (increasing from ~2% at 1500 K to ~10% at 1600 K over the pressure range of 100-300 Torr).…”
Section: Branching Ratiossupporting
confidence: 89%
See 3 more Smart Citations
“…The mechanism for the formation of propargyl (C3H3) radicals is proposed to be via formyl allene (INT3) → C3H3 + HCO (P3) by Tian et al 36 while Sendt et al 35 proposed via the formation CH3CCH (P2) → C3H3 + H pathway. The proposed pathway via CH3CCH resonates well with the conclusion of recent works by Cheng et al (2017) 98 and by Weber et al 32 who pointed out that C3H3 radical is mainly formed from C3H4 isomers rather than from furan directly. Moreover, Urness and co-workers 31 determined the fraction of propargyl (C3H3) radical to propyne (CH3CCH) using a silicon carbide microtubular reactor and found that the [C3H3]/[CH3CCH]) branching ratio (increasing from ~2% at 1500 K to ~10% at 1600 K over the pressure range of 100-300 Torr).…”
Section: Branching Ratiossupporting
confidence: 89%
“…[b] 7.9×10 14 0.00 35164.7 P4 → Furan [c] 1.7×10 -10 0.00 0.0 P5 → Furan [c] 1.7×10 -10 0.00 0.0 [a] Units of [s −1 ] for first-order reactions and [cm 3 molecule −1 s −1 ] for second-order reactions. [b], [c] Taken from the works of Sendt et al 31 and Tian et al 32 , respectively, for the barrierless channels.…”
Section: Kinetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…HPAs (heteropoly acids) with superb strong acidity are extensively used as economic and environmental catalysts in organic synthesis [28][29][30][31][32]. In particular, phosphotungstic acid (HPW, H 3 PW 12 O 40 ) has a tetrahedral PO 4 core in the center of the anion structure, surrounded by twelve WO 6 polyhedra via oxygen atoms to link each other, which exhibits excellent catalytic activity for upgrading biomassderived compounds into different valuable chemicals and biofuels [33,34].…”
Section: Introductionmentioning
confidence: 99%